Smart village: Evaluating the role of Siskeudes management in enhancing village fund accountability - Mahmud, Amir; Susilowati, Nurdian; Handayani, Bestari Dwi; Leonita, Ayu; Santoso, Arif (Edelweiss Applied Science and Technology, 2024)
Smart villages are basically about how rural communities make the best use of ICT and social innovation to create accountability. Rural communities worldwide are looking for solutions to improve suboptimal community services. Information and communication technology applications allow rural communities to improve their quality of life and provide excellent service. Smart villages are basically about how rural communities make the best use of ICT and social innovation to create accountability. The objective of this study is to investigate the impact of Siskeudes operator’s competence, training quality, and internal control on the accountability of village fund management mediated by Siskeudes usage. The study employed a questionnaire survey with village officials in Ketanggungan Sub-district, Brebes Regency, with a sample size of 105 people, decided employing the purposive technique. Descriptive analysis was used to clarify the general perceptions of the survey respondents and path analysis to explore the direct and indirect effect. The results point out a direct effect of Siskeudes operator’s competence, training quality, system of internal control, and Siskeudes usage on the village fund accountability. Furthermore, Siskeudes usage mediates Siskeudes operator’s competence, training quality, and system of internal control on accountability of village fund management. To ensure effective accountability reporting from village governments, it is important to strengthen officials’ competencies, provide targeted training to improve operational efficiency, and implement robust control systems. In addition, the development of an integrated village financial system can facilitate transparent reporting and minimize the risk of misappropriation of funds.